Effects of corn replacement by sorghum in broiler diets on performance and intestinal mucosa integrity - Torres, K. A. A.; Pizauro, Jr. [UNESP]; Soares, Christiane Pienna [UNESP]; Silva, T. G. A. [UNESP]; Nogueira, W. C. L.; Campos, D. M. B.; Furlan, R. L.; Macari, Marcos [UNESP] (My University, 2013)
The effect of replacing corn with lowtannin sorghum on broiler performance, carcass yield, integrity of mucosa of small intestine segments, and activity of membrane enzymes of the jejunum is investigated. A total of 594 male Cobb-500 broiler chicks were randomly assigned to 3 dietary treatments: 100% corn (control), 50% corn replacement with low-tannin sorghum (low sorghum), and 100% corn replacement with low-tannin sorghum (high sorghum). Body weight gain, feed consumption, feed conversion, and carcass yield were determined at 7, 21, and 42 d, and segments of the small intestine were collected. Feed conversion and weight gain were impaired at d 42 in broilers fed the high-sorghum diet, but no differences were observed for carcass yield among the treatments (P > 0.05). Crypt cell mitotic index of the jejunum and ileum at d 21 and 42 was lower in broilers fed the control diet than in those fed low- and high-sorghum diets (P < 0.05). Aminopeptidase activity was higher in broilers fed the control diet than in those fed low- and high-sorghum diets irrespective of age (P < 0.05). Conversely, intestinal alkaline phosphatase activity in the small intestine did not differ among the dietary treatments (P > 0.05). Our results indicate that 50% corn replacement with low-tannin sorghum is suitable for broiler diets, whereas 100% corn replacement with low-tannin sorghum had negative effects on the intestinal mucosa and performance of broilers at 42 d. © 2013 Poultry Science Association Inc.
Keywords: Aminopeptidase; Broiler performance; Intestinal morphometry; Mitotic index; Sorghum; alkaline phosphatase; aminopeptidase; animal; animal disease; animal food; cell proliferation; chicken; controlled clinical trial; controlled study; cytology; diet; genetics; growth, development and aging; intestine mucosa; maize; male; metabolism; physiology; randomized controlled trial; sorghum; weight gain; Alkaline Phosphatase; Aminopeptidases; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Cell Proliferation; Chickens; Diet; Intestinal Mucosa; Male; Weight Gain; Zea mays